1996
DOI: 10.1152/ajpgi.1996.271.5.g849
|View full text |Cite
|
Sign up to set email alerts
|

Participation of 5-HT3, 5-HT4, and nicotinic receptors in the peristaltic reflex of guinea pig distal colon

Abstract: The roles of 5-hydroxytryptamine3 (5-HT3), 5-HT4, and nicotinic receptors in the peristaltic reflex were investigated in isolated segments of guinea pig distal colon. The reflex assessed by measuring the propulsion of solid pellets, was affected neither by 5-HT3-selective antagonists (ondansetron granisetron) nor by 5-HT4-selective antagonists (SDZ-205-557, GR-113808A, SB-204070) applied individually (1.0 microM); nevertheless, the reflex was inhibited by combining these antagonists or by applying a 5-HT3/5-HT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
98
4
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(105 citation statements)
references
References 0 publications
2
98
4
1
Order By: Relevance
“…Among others, synaptic transmission through nAChRs affects the initiation and/or propagation of the peristaltic reflex (Galligan and Burks, 1986;Kadowaki et al, 1996), the secretion of gastrin, somatostatin and gastric acid (Nishi et al, 1985;Cho et al, 1987;Wong and Ogle, 1995), the motility of the duodenal wall, and the secretion of fluids (Fandriks et al, 1994(Fandriks et al, , 1995.…”
Section: Nachrs In the Control Of Gut Functionmentioning
confidence: 99%
“…Among others, synaptic transmission through nAChRs affects the initiation and/or propagation of the peristaltic reflex (Galligan and Burks, 1986;Kadowaki et al, 1996), the secretion of gastrin, somatostatin and gastric acid (Nishi et al, 1985;Cho et al, 1987;Wong and Ogle, 1995), the motility of the duodenal wall, and the secretion of fluids (Fandriks et al, 1994(Fandriks et al, , 1995.…”
Section: Nachrs In the Control Of Gut Functionmentioning
confidence: 99%
“…A subset of myenteric interneurons is serotonergic (8,13,22,29,31,76,77); therefore, 5-HT antagonists can block peristaltic reflexes by inhibiting enteric serotonergic neurotransmission (46,60,82) as well as by interfering with the paracrine stimulation of IPANs. 5-HT from EC cells also plays a role in extrinsic sensation by stimulating extrinsic primary afferent nerves (2,39,40).…”
mentioning
confidence: 99%
“…29,36,49 In contrast, others demonstrated that nicotinic receptors are not essential in mediating peristalsis of the guinea pig distal colon. 50,51 They showed that hexamethonium temporarily arrested peristalsis and fecal pellet propulsion.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the inserted pellets are well advanced distally in vitro preparations of the guinea pig distal colon, but not rat distal colon. [27][28][29] Our preliminary study also showed that the rat distal colon failed to propel fecal pellets in vitro (unpublished observations). Our laboratory has produced a number of studies in a rat model, demonstrating that transection of parasympathetic PN significantly delayed colonic transit time, while the transection of sympathetic hypogastric nerve significantly increased colonic motility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation